Digital tooth reconstruction: An innovative approach in forensic odontology - Johnson, Abraham (J Forensic Odontostomatol, 2019)
In mass disasters, accidents and crime investigations, where human remains are decomposed, charred or skeletonized, teeth may dislodge due to post-mortem loss or due to mishandling of evidence during the manipulation of skeletal and dental remains. Thus, the identification process is hampered due to the loss of dental evidence. In these situations, forensic tooth reconstruction may aid in the identification process. Forensic tooth reconstruction (FTR) refers to the process that aims to reconstruct the morphology of the missing tooth from the skeletal remains from the intra-alveolar morphology of the dental socket. The study is an innovative attempt to develop a digital approach to reconstruct three-dimensional (3D) printed tooth models through recording intra-alveolar morphology of empty dental sockets which simulate the teeth which are missing post-mortem. An experimental study was conducted on the human mandible, where using volumetric scanning, 3D scanning and printing techniques the tooth was reconstructed from the intra-alveolar morphology of the socket. Through metric analysis and qualitative congruency testing it was established that there was minimal discrepancy between natural tooth and 3D printed tooth. It was determined that teeth missing post-mortem do not necessarily invalidate the identification process. Digital FTR gives accurate results with minimum error.